FORMULATION OF TRICHODERMA VIRENS ORIGIN OF ACEH COCOA CONTROLLING BLACK POD DISEASE CAUSED BY PHYTOPHTORA PALMIVORA - TJUT CHAMZURNI; RINA SRIWATI; RIZKY MUARIF; BUNI AMIN; ABDUH ULIM (Syiah Kuala University, 2014)
Trichoderma virens have been isolated from rooting cocoa in Aceh and in the laboratory have been reported capable of inhibiting the growth of P. palmivora in vitro. However, the formulations of T. virens from Aceh can be used as an alternative product for farmers in controlling black pod disease of cocoa. This research was conducted t the Laboratory of Plant Pathology College of Agriculture Syiah Kuala University and cocoa fruit samples obtained from cocoa plantations owned by farmers in Pidie Jaya District of Aceh. The purpose of the study was to obtain an application formulations strains of T. virensfrom Aceh, as one of the biological control study consisted of seven treatments, namely W (water), Pest (Mancozeb Fungicide), Det (Detergent), Det+Tv( detergent+strainsof T.virens), P+Tv (Adhesive +strainsof T.virens), Co+Tv( Corn Oil+strainsof T.virens), Po+Tv (Palm oil+strainsof T.virens) and each treatment was repeated 10 times to obtain70 experimental units. The parameters observed incubation period, disease incidence (%), and the diameter of the spots (cm). Application results show that the strains of T. virens Origin Aceh effective in controlling P. palmivora on cocoa pods and the best formulation in controlling P. palmivora on cocoa pods are corn oil+T. virens formulation (Co +Tv) compared with other formulations are characterized by the length of the incubation period, the low incidence of P. palmivora disease, and the small diameter of the spots on the cocoa pods.